Peningkatan keterampilan menulis paragraph melalui penerapan kegiatan menulis jurnal bagi siswa Kelas VIII SMP Negeri 5 Praya - Heppy Suriadin Sorenggana (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2018)
Class Action Classification with 2 cycles to know the usefulness of the implementation of journal writing activities to improve the ability of writing pragraf to students of class VIII SMPN 5 Praya year 2015/2016, through qualitative descriptive approach, data collection method used observation, interview, and documentation. The results showed that there was an increase in students' writing activity, ie 36% in the first cycle, 48% in cycle two, and 66% in cycle three. It was concluded that there was an increase of writing ability of pragraf to grade VIII students of SMPN 5 Praya through the application of journal writing activity.